Current residual‐based method for open‐circuit fault diagnosis in single‐phase PWM converter. Issue 14 (12th October 2018) - Xie, Dong; Pu, Junkai; Ge, Xinglai
Abstract : This study presents an open‐circuit fault diagnosis method based on residual changing rate instead of the specific switching signals injection for single insulated gate bipolar transistor in the single‐phase pulse‐width modulation (PWM) converter. Firstly, the mixed logical dynamic model of the single‐phase PWM converter is established to obtain the residual of grid‐side current. Then, the characteristics of residual changing rate are obtained through the combination of theoretical analysis and simulation results. Furthermore, the diagnostic variables based on the residual changing rate are defined by the isolation of switching signals. Also compared with the threshold, fault detection and location can be accomplished. The proposed diagnosis method does not need extra sensors and injection of special switching signals, which can reduce the diagnosis complexity and does not affect operating state of the system. Furthermore, the diagnostic method has fast diagnosis speed and robustness against false alarms under different operation conditions. Experimental results have illustrated the validity and feasibility of the proposed diagnostic method.